L’islam dans l’école : une frontière invisible ? - Samia Langar (Recherches en Éducation)
French law prohibiting the wearing of ostentatious signs in schools seems to have put an end to the “problem” of the veil. However, a daily scene is now seen at the doors of schools hosting French students of Muslim culture and religion: young girls coming veiled take off their veil before entering their school and dress as soon they leave. These gestures on the doorstep of the school symbolically mark lines of passage that are also dividing lines: between school space and public space, between regimes of visibility, between particularism and universalism, between inclusion and exclusion. More generally, these dividing lines undermine and re-interrogate secularism itself and the universal it claims to be.